Selective Fluorescence Imaging of Cancer Cells Based on ROS‐Triggered Intracellular Cross‐Linking of Artificial Enzyme. Issue 14 (10th February 2022) - Di, Yufei; Zhang, Endong; Yang, Zhiwen; Shen, Qi; Fu, Xuancheng; Song, Gang; Zhu, Chuanwei; Bai, Haotian; Huang, Yiming; Lv, Fengting; Liu, Libing; Wang, Shu
Abstract: Inside living cells, regulation of catalytic activity of artificial enzymes remains challenging due to issues such as biocompatibility, efficiency, and stability of the catalyst, by which the practical applications of artificial enzymes have been severely hindered. Here, an artificial enzyme, PTT‐SGH, with responsiveness to reactive oxygen species (ROS), was obtained by introducing a catalytic histidine residue to pentaerythritol tetra(3‐mercaptopropionate) (PTT). The artificial enzyme formed large aggregates in cells via the intracellular ROS‐mediated oxidation of thiol groups. The process was significantly facilitated in tumor cells because of the higher ROS concentration in the tumor microenvironment. The catalytic activity of this artificial enzyme was intensively enhanced through deprotonation of cross‐linked PTT‐SGH, which showed typical esterase activities. Selective fluorescence imaging of tumor cells was achieved using the artificial enzyme to trigger the cleavage of the ester bond of the caged fluorophore inside living cells. Abstract : An artificial enzyme that responds to intracellular reactive oxygen species (ROS) was designed through introducing a catalytic histidine residue at one of the thiols of pentaerythritol tetra(3‐mercaptopropionate). The artificial enzyme could in situ cross‐link to form an assembled structure that could trigger the cleavage of the ester bond of pro‐fluorophore and activate the turn‐on fluorescence inside cancer cells for selective diagnosis.